Kajian Tarikan Pergerakan Lalu Lintas Pada Guna Lahan Komersial Koridor Jalan Prof. Sudharto Semarang - Jati, Andi Nugroho (JURNAL PEMBANGUNAN WILAYAH & KOTA, 2012)
The development of a center of education in Tembalang has converted housing areas along the corridor of Jalan Ngesrep V – Jalan Prof. Sudharto into commercial areas providing trade and services. The conversion has also created an increase of trip attraction in the corridor. The study aims to examine the influence of the commercial activities on the trip attraction along the corridor. The study identifies the land use and commercial activities in the corridor, analyzes the trip and its road network pattern, and models the trip generated by the commercial activities. The study uses descriptive analysis to analyze the conversion of land use, activity and trip pattern. The study also applies quantitative analysis to establish a model of the trip attraction using stepwise regression. Analysis concluded that the increase of commercial activities along the study corridor has cause an increase of traffic flow. Trip attraction modeling has found three variables which affect the amount of attraction created; they are: (1) number of vehicle(s) owned; a 100 percent of increase in the number will raise trip attraction by 24,04 percent, (2) distance travelled; a 100 percent of increase in the number will raise trip attraction by 0,4 percent, and (3) amount of money spent; a 100 percent of increase in the number will raise trip attraction by 0,004195 percent. The overall influence of the three variables to the increase in trip attraction is 31,4 percent.